THE APPLICATION OF SEM-EDS FOR THE SURFACE TEXTURE OF FORAMINIFERA: IDENTIFICATION OF EARLY DIAGENESIS OF REWORKED L. DIMIDIATUS WITHIN MODERN COASTAL DEPOSITS - Rahmadi Hidayat; Sarju Winardi; Akmaluddin Akmaluddin (BULLETIN OF THE MARINE GEOLOGY, 2023)
Sediment recycling has been known to occur within Quaternary coastal barriers of the greater Coorong Coastal Plain, southern Australia. A high degree of reworking of skeletal carbonates from Late Pleistocene deposits (Robe Range) is evident based on the novel application of amino acid dating of the single-foraminifera species Lamellodiscorbis dimidiatus. More importantly, some apparently transparent, well-preserved tests indicate anomalously high extents of amino acid racemization, implying that reworked fossils could not be easily distinguished based on taphonomic signatures such as corrosion. Here, we examine the surface microtexture of this species, constrained with well-preserved specimens, on a modern beach of Canunda, southern Australia, using scanning electron microscopy coupled with energy dispersive spectroscopy (SEM-EDS). The aim is to identify surface features of foraminifera in more detail, capturing signs of early diagenesis associated with weakly consolidated Late Pleistocene coastal barriers. The results reveal that some well-preserved tests show localized blocky calcite cementation, most notably within intraseptal spaces or impact sites. The EDS spectra of cement indicate lower Mg content than unaltered foraminifera surface. This suggests low-Mg calcite precipitation due to meteoric diagenesis experienced by the onshore Late Pleistocene coastal barrier. It implies that these foraminifera shells are reworked fossils originated from older successions and were subsequently redeposited within the present-day beach. SEM-EDS used in this study demonstrates its capability in examining small-scale carbonate diagenesis products beyond the traditional binocular microscope. Thus, this tool is recommended to aid amino acid dating in detecting reworked fossils.